Transformasi Politik Gerakan Aceh Merdeka (GAM) - Nurhasim, Moch (Jurnal Penelitian Politik, 2009)
The political transformation of Gerakan Aceh Merdeka (GAM) is a process to change GAM as a "military" power into a civil power. This fundamental process is a part of conflict resolution ofAceh that has been conducted for about 32 years. This political transformation highlights some forms of change of GAM's organizations, character, and behavior in the post-MoU Helsinki.